System of Proof Against First to Use of Trademarks in Lawsuit for Cancelation of Trademark Registration by Bad Faithz - Triyana, Usi; Ramadhan Baried, Rizky (Journal of Private and Commercial Law, 2023)
This trademark dispute originated with the plaintiff who claimed to be the owner and origin user of the Tempo Gelato brand but did not register himself as the owner. On the other hand, the defendant, who was originally a business partner of the plaintiff, registered herself as the owner of the Tempo Gelato brand, while business was running by them. This dispute was examined by commercial court up to the cassation level with the object of examination being allegations of bad faith by the defendant in registering the Tempo Gelato brand. The formulation of the problem is: 1. What is the proof with the first-to-use argument in canceling the registration of mark with bad faith? How is the review of the procedural law against the decision that granted the counterclaim, while rejecting the lawsuit? This research is a normative one, by analyzing secondary data sources through qualitative analysis. The result is because the court did not find clear evidence regarding the gelato business cooperation agreement, it could not be proven that there was first to use by plaintiff, on the other hand because private procedural law seeks formal evidence, the defendant is considered the owner of the brand base on the fits to file principle. Secondly, the procedural law allows if the lawsuit is not declared unacceptable, then if it is rejected and vice versa, the counterclaim is accepted, it is legal consequence of the existence of a counterclaim which can be proven to have a causal relationship.